Odpowiedź :
Odpowiedź:
Zawsze zaczynam od podstawy dolnej i dalej zgodnie z ruchem wskazówek zegara:
2. a)
b + b + a + b + a + b + a + a = 4a + 4b
b)
b + a + a + b + a + a + b - a + b + a = 4a + 4b
c)
b + a + b + a + b - 2a + b + a + a = 2a + 4b
d)
a + b + a + b + a + b - a + b + b - a +a + b = 2a + 6b
e)
b + a/2 + b + a/2 + a + b - a/2 + b - a/2 + b + a/2 + a + b + a/2 + a = 4a + 6b
f)
b + a/2 + a + b + a/2 + b - a/2 + a + b + a/2 + a + a/2 + a = 6a - a/2 + 4b =
= 11a/2 + 4b
g)
a + a/2 + b + a + b + a/2 + a + a/2 + b + a + a + b + a/2 = 7a + 4b
h)
b + a + a + b + a + a/2 + b + a + b + a + a/2 + a = 7a + 4b
Szczegółowe wyjaśnienie:
Zawsze zaczynam od podstawy dolnej i dalej zgodnie z ruchem wskazówek zegara:
2. a)
b + b + a + b + a + b + a + a = 4a + 4b
b)
b + a + a + b + a + a + b - a + b + a = 4a + 4b
c)
b + a + b + a + b - 2a + b + a + a = 2a + 4b
d)
a + b + a + b + a + b - a + b + b - a +a + b = 2a + 6b
e)
b + a/2 + b + a/2 + a + b - a/2 + b - a/2 + b + a/2 + a + b + a/2 + a = 4a + 6b
f)
b + a/2 + a + b + a/2 + b - a/2 + a + b + a/2 + a + a/2 + a = 6a - a/2 + 4b =
= 11a/2 + 4b
g)
a + a/2 + b + a + b + a/2 + a + a/2 + b + a + a + b + a/2 = 7a + 4b
h)
b + a + a + b + a + a/2 + b + a + b + a + a/2 + a = 7a + 4b